Primary jejunal malignant melanoma presenting as intussusception: a rare case report - Kumari, N. Sreemani; Nandyala, Venkat Narsimha Reddy; Devi, K. Rama; Nirmala, B. Vijaya; Krishna, L.; Masood, S. V.; Kumar, O. Shravan (International Surgery Journal, 2016)
A 60-year-old male patient presented with complaints of pain abdomen and vomiting. Clinical examination revealed a mass in hypogastrium extending up to right iliac fossa. Exploratory laparotomy showed a jejuno-jejunal intussusception with lead point mass lesion presenting as sub-acute intestinal obstruction. Per-operative findings revealed a blackish mass. A provisional diagnosis of melanoma was made, which was subsequently confirmed on histopathology and immunohistochemistry. Gastrointestinal (GI) melanomas are rare tumors, involving ileum and anus. Jejunum is a rare site amongst the small intestinal melanomas. Intussusception is common in the pediatric age group. We report a rare case of primary jejunal malignant melanoma, presenting with sub-acute intestinal obstruction due to jejuno-jejunal intussusception. Primary melanomas have a pre-deliction for males, involve ileum and have a poor prognosis than the metastatic GI or primary cutaneous melanomas. Surgery is the treatment of choice.